Corpus-based analyses of the problem-solution pattern : a phraseological approach - Flowerdew, Lynne (Studies in corpus linguistics, 2008)
This book reports research on the Problem-Solution rhetorical pattern, which has to date received very little attention in corpus-based studies. Insights from genre analysis and systemic-functional grammar are also applied to the analysis of the Problem-Solution pattern, thus moving towards a more multi-faceted analysis of corpus data. The pattern is investigated in two specialized corpora of technically-oriented report writing, a professional corpus and a student corpus, using a key word and key-key word analysis. Phraseological analyses of key words in both corpora are presented. Data show t.